2021
DOI: 10.1098/rsos.201598
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency sampling rates are effective to record bottlenose dolphins

Abstract: Acoustic monitoring in cetacean studies is an effective but expensive approach. This is partly because of the high sampling rate required by acoustic devices when recording high-frequency echolocation clicks. However, the proportion of echolocation clicks recorded at different frequencies is unknown for many species, including bottlenose dolphins. Here, we investigated the echolocation clicks of two subspecies of bottlenose dolphins in the western South Atlantic Ocean. The possibility of recording echolocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Outside the beam, the low-frequency components suffer less attenuation and appear in the frequency spectrum [35]. Thus, low-frequency components are expected to be predominant when free-ranging dolphin vocalizations are recorded since they are mainly off-axis of the transmitting beam [36]. It is worth recalling that the CoPiDi hydrophone was developed with just the main aim of measuring free-ranging dolphin vocalizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside the beam, the low-frequency components suffer less attenuation and appear in the frequency spectrum [35]. Thus, low-frequency components are expected to be predominant when free-ranging dolphin vocalizations are recorded since they are mainly off-axis of the transmitting beam [36]. It is worth recalling that the CoPiDi hydrophone was developed with just the main aim of measuring free-ranging dolphin vocalizations.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth recalling that the CoPiDi hydrophone was developed with just the main aim of measuring free-ranging dolphin vocalizations. Moreover, based on the abovementioned analyses, a study by Romeu et al showed that a sampling frequency of 48 kHz (and thus recorded bandwidth = 24 kHz) may be effective for recording the entire acoustic repertoire of Turpsiops truncatus when employed in studies analyzing and quantifying the presence/absence of the single animal or a population of cetaceans in a specific location [36]. For all the situations described above, the proposed hydrophone appears to be a suitable tool for recording dolphin's vocalization, especially considering its low cost.…”
Section: Discussionmentioning
confidence: 99%
“…Outside of the beam, the low-frequency components experience less attenuation and appear in the frequency spectrum 35 . Therefore, low-frequency components are expected to be predominant when free-ranging dolphin vocalizations are recorded since they are mainly off-axis of the transmitting beam 36 . In the current study, bottlenose dolphin vocalizations were recorded with no regard to specific distance or orientation from the hydrophone.…”
Section: Data Recordsmentioning
confidence: 99%
“…In the current study, bottlenose dolphin vocalizations were recorded with no regard to specific distance or orientation from the hydrophone. Based on these considerations, it was determined that the frequency of 48 kHz could be effective for recording the entire acoustic repertoire of Tursiops truncatus , including echolocation signals, in studies analyzing the occurrence or distribution of individuals in a population or at a specific location when the presence or absence data are sufficient 36 . These observations indicate that the present database recorded at 192 kHz could be suitable for the majority of dolphin vocalization analyses.…”
Section: Data Recordsmentioning
confidence: 99%